Social Media Content Preferences and Political Participation among Nigerian Youths - Mande Ande Mande; Lambe Kayode Mustapha; Bahiyah Omar; Maryam Lasisi Mustapha; Ismail Sheikh Yusuf Ahmed (Romanian Journal of Communications and Public Relations, 2022)
This study examines the influence of social media content preferences on political participation in Nigeria’s relatively nascent democracy. Due to mixed conclusions on the influence of news and entertainment preferences on political participation, we sampled 434 youths aged 18-35 in a Nigerian northern state, to investigate the differential influence of diverse social media content consumption on political participation. Incorporating the moderating and mediating influences of political efficacy and incidental news exposure, findings confirm that news and entertainment preferences are positive, significant predictors of political participation among respondents. While political efficacy moderated the influence of news preference on political participation, incidental news exposure did not mediate the influence of entertainment preference on political participation. We recommend further investigation into the influence of content preferences on political participation among Nigerian youths who constitute considerable members of the nation’s electorate.